2014
DOI: 10.3390/ijms15034714
|View full text |Cite
|
Sign up to set email alerts
|

Current Progress in Bioactive Ceramic Scaffolds for Bone Repair and Regeneration

Abstract: Bioactive ceramics have received great attention in the past decades owing to their success in stimulating cell proliferation, differentiation and bone tissue regeneration. They can react and form chemical bonds with cells and tissues in human body. This paper provides a comprehensive review of the application of bioactive ceramics for bone repair and regeneration. The review systematically summarizes the types and characters of bioactive ceramics, the fabrication methods for nanostructure and hierarchically p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
143
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 262 publications
(150 citation statements)
references
References 108 publications
0
143
0
4
Order By: Relevance
“…On the other hand, the pH value of culture environment affects the cell’s behaviors and a much higher or lower pH value is harmful. Previous studies showed that a more stable pH value can stimulate metabolic activity, proliferation, and differentiation of osteoblasts [54,55]. In this study, the β-Ca 2 SiO 4 scaffolds sintered at 1200 °C induced a more stable microenvironment, which might contribute the enhanced proliferation and differentiation of rBMSCs.…”
Section: Discussionmentioning
confidence: 55%
“…On the other hand, the pH value of culture environment affects the cell’s behaviors and a much higher or lower pH value is harmful. Previous studies showed that a more stable pH value can stimulate metabolic activity, proliferation, and differentiation of osteoblasts [54,55]. In this study, the β-Ca 2 SiO 4 scaffolds sintered at 1200 °C induced a more stable microenvironment, which might contribute the enhanced proliferation and differentiation of rBMSCs.…”
Section: Discussionmentioning
confidence: 55%
“…While each will be surveyed individually below, it should be noted that many strategies employ a combination of these materials-termed "composites" or "hybrids" -in an attempt to mitigate their individual limitations. For more comprehensive information on this topic, the reader is directed to several extensive reviews of bone scaffold materials and the biomechanical/biophysical constraints thereof [14][15][16].…”
Section: Scaffolding Materialsmentioning
confidence: 99%
“…A hydroxyapatite (Ca 10 (PO 4 ) 6 (OH) 2 : HAp) possesses bone regenerative and biodegradable characteristics 1,2 , and it may be applied to the drug carriers 3,4 and scaffold 1,5 . Previously, HAp has been prepared by many chemical routes 6 .…”
Section: Introductionmentioning
confidence: 99%